PERANCANGAN PENGEMBANGAN PEMASARAN KOPI DI KECAMATAN SITUJUAH LIMO NAGARI KABUPATEN LIMA PULUH KOTA PROVINSI SUMATERA BARAT - Helentina Situmorang; Elva Rahmi Fitri; Misfit Putrina; Noveri Noveri; Andi Eviza; Amaliyah Syariyah (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Robusta coffee is a leading commodity in Lima Puluh Kota Regency and is highly sought after by the public. However, farmers still sell more cherry coffee than green beans. The purpose of this study was to describe the problems faced by coffee farmers in Situjuah Limo Nagari District, who sell more cherry coffee than green beans, and to design a marketing strategy for green beans in Situjuah Limo Nagari District. This research was conducted from July to October 2025 in Situjuah Limo Nagari District. The location was chosen because there are farmers selling green beans or cherry coffee in Situjuah Limo Nagari District. The research sample was purposive, selecting coffee farmers selling green beans or cherry coffee. The analysis used descriptive qualitative methods involving robusta coffee farmers and the local government. The results of the study indicate a marketing strategy for developing robusta green beans, starting from the upstream stage (good cultivation practices), coffee processing machines, the need for local government support for expanding the marketing of robusta green beans, and digital marketing through social media and online stores. Keyword: robusta coffee; marketing; green beans. Abstrak: kopi robusta menjadi komoditas unggulan di Kabupaten Lima Puluh Kota dan banyak diminati masyarakat. Akan tetapi, petani masih banyak menjual kopi ceri dibandingkan kopi green bean. Tujuan dari penelitian ini adalah mendeskripsikan permasalahan petani kopi Kecamatan Situjuah Limo Nagari yang lebih banyak menjual kopi ceri dibandingkan kopi green bean  dan merancang pengembangan pemasaran kopi green bean di Kecamatan Situjuah Limo Nagari. Penelitian ini dilaksanakan pada Juli-Oktober 2025 di Kecamatan Situjuah Limo Nagari. Penentuan lokasi karena Kecamatan Situjuah Limo Nagari ada petani yang menjual kopi green bean atau ceri. Penentuan sampel penelitian dengan purposive yaitu petani kopi yang menjual kopi green bean atau ceri. Analisis yang digunakan deskriptif kualitatif melibatkan petani kopi robusta dan pemerintah daerah. Hasil penelitian menunjukkan perancangan pengembangan pemasaran kopi robusta green bean dengan yang dimulai dari hulu (cara budidaya yang baik), mesin pengolah kopi, perlunya dukungan pemerintah daerah untuk perluasan pemasaran kopi robusta green bean hingga pemasaran secara digital melalui media sosial dan toko online. Kata kunci: kopi robusta; pemasaran; green bean.